Are legal values gendered? Gender differences in support for judicial independence in Hong Kong - Lee, Man Yee Karen (International journal of law, crime and justice, 2020)
Gender allegedly influences attitude and behaviour. Compared to the vast literature on gender and political culture, the role of gender in shaping legal values remains under-researched. Based on data from a 2015 survey in Hong Kong, this study fills a gap by ascertaining the gender effect on support for judicial independence. It found that, despite the significance of migrant status, education level and occupation, gender alone predicts support for judicial independence. Second, all things being equal, women are less supportive of judicial independence than men. Third, Hong Kong-born male professionals with tertiary education and China-born female manual workers with primary education or below registered the highest and lowest degree of support for judicial independence, respectively. Given the steady inflow of Mainland Chinese migrants after the city returned to Chinese rule in 1997, many of them wives of Hong Kong husbands, these findings raised questions about the former British colony's evolving legal culture.